Impacts of tropical deforestation on local temperature and human well-being perceptions. (September 2018) - Wolff, Nicholas H.; Masuda, Yuta J.; Meijaard, Erik; Wells, Jessie A.; Game, Edward T.
Highlights: 477 villages throughout Kalimantan were surveyed about forest health benefits. The most frequent answer was maintenance of cool local temperatures. Perceptions were driven by deforestation and local temperature. Results point to possible threat of heat impacts on health. Policy should incorporate human health when considering land use. Abstract: The combined effects of changes in climate and land cover expose millions of people to an increased likelihood of heat illness. Impacts of heat stress on health have primarily been quantified for urban environments, particularly in developed countries. Far less is known in other settings, including the effects of ongoing tropical deforestation on local temperature and its consequences for people living in these rapidly changing landscapes. Here, we explore links between deforestation and self-reported human health and well-being in the tropical landscapes of Borneo. We use extensive social surveys from nearly 500 villages throughout Kalimantan (Indonesian Borneo) that asked whether forests were important for health, and why. The most frequent answer viewed forests as important for maintaining cool local temperatures (volunteered by 28% of 4634 respondents). Using boosted regression tree analysis incorporating spatial metrics of deforestation and temperature, we found that villagers were more likely to report this cooling effect if they were from villages with higher or more variable temperatures, and in recently deforested or fragmented landscapes. Our results highlight the role of forests in regulating the local climate. This ecosystem service is highly threatened, and yet increasingly vital for avoiding heat illness and enabling adaptation to global climate change.